Lack of sleep as a contributor to obesity in adolescents: impacts on eating and activity behaviors - Chaput, Jean-Philippe; Dutil, Caroline (Université d'Ottawa | University of Ottawa, 2016)
Abstract Background Sleep is an important contributor to physical and mental health; however, chronic sleep deprivation has become common in adolescents, especially on weekdays. Adolescents aged 14–17 years are recommended to sleep between 8 and 10 h per night to maximize overall health and well-being. Although sleep needs may vary between individuals, sleep duration recommendations are important for surveillance and help inform policies, interventions, and the population of healthy sleep behaviors. Long sleepers are very rare among teenagers and sleeping too much is not a problem per se; only insufficient sleep is associated with adverse health outcomes in the pediatric population. Causes of insufficient sleep are numerous and chronic sleep deprivation poses a serious threat to the academic success, health and safety of adolescents. This article focuses on the link between insufficient sleep and obesity in adolescents. Discussion This “call to action” article argues that sleep should be taken more seriously by the public health community and by our society in general, i.e., given as much attention and resources as nutrition and physical activity. Not only that having a good night’s sleep is as important as eating a healthy diet and being regularly physically active for overall health, but sleeping habits also impact eating and screen time behaviors and, therefore, can influence body weight control. Summary Short sleep duration, poor sleep quality, and late bedtimes are all associated with excess food intake, poor diet quality, and obesity in adolescents. Sleep, sedentary behavior, physical activity and diet all interact and influence each other to ultimately impact health. A holistic approach to health (i.e., the whole day matters) targeting all of these behaviors synergistically is needed to optimize the impact of our interventions. Sleep is not a waste of time and sleep hygiene is an important factor to consider in the prevention and treatment of obesity.